Distribution of Vicine, Convicine and Levodopa in Faba Bean Plant Tissues Determined by UltraHigh Performance Liquid Chromatography-Electrospray Ionization Mass Spectrometry - Devini De Silva; Yong Liu; Mark A Smith; Albert Vandenberg; Haixia Zhang (Journal of Chromatography Open, 2024)
Faba bean is an emerging pulse crop for the Canada Prairies and is becoming an increasingly important source of plant sourced protein. It also has a high content of levodopa (up to 0.1 % of the dry seed weight), a nutraceutical compound for treating Parkinson's Disease (PD). The presence of pyrimidine glycosides, vicine and convicine, however, restricts the use of faba due to their potential to cause favism in susceptible individuals. For the rapid separation and quantification of levodopa, vicine and convicine, a 5-min ultrahigh performance liquid chromatography-electrospray ionization mass spectrometry method (UHPLC-ESI MS) was developed. This method provided a wide linear range of quantification (4.8 nM to 60 µM for vicine, and 6.0 nM to 24 µM for convicine and levodopa), and low limit of detection (1.2 to 3.0 nM). The method was applied in the analysis of diverse faba bean samples, from dehulled mature faba bean and seed coat, to fresh plant tissues such as flowers, leaves, stems, roots and pods. The results indicated that fresh faba bean plant tissues, such as leaves and flowers, had the highest concentration of levodopa and low level of VC, which makes them an alternative source of plant-based l-DOPA with potential as a food-based treatment for Parkinson's Disease.